Global risk and the dollar - Georgios Georgiadis; Gernot J. Müller; Ben Schumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
The dollar is a safe-haven currency and appreciates when global risk goes up. We investigate the dollar's role for the transmission of global risk to the world economy within a Bayesian proxy structural vectorautoregressive model. We identify global risk shocks using high-frequency asset-price surprises around narratively selected events. Global risk shocks appreciate the dollar, induce tighter global financial conditions and a synchronized contraction of global economic activity. We benchmark these effects against counterfactuals in which the dollar does not appreciate. In the absence of dollar appreciation, the contractionary impact of a global risk shock is much weaker, both in the rest of the world and the US. For the rest of the world, contractionary financial channels thus dominate expansionary expenditure switching when global risk rises and the dollar appreciates.
Keywords: F31; F42; F44; 330; Dollar exchange rate; global risk shocks; international transmission; Bayesian proxy structural VAR